Osteosarcoma with atypical location in an elderly female patient - Ogata, Daniel Cury; Moreira, Rafael Saviolo; Gomes, Alberto Ramos; Pereira Neto, Elisiário; Sezerino, Daniel Oséias; Hirano, Matsue Braga (Autopsy and Case Reports, 2011)
Osteosarcoma most frequently affects long bones, particularly around theknee, and is therefore rare in the forearm. We report the case of a 67-year-oldwoman presenting with progressive lesion of the distal radius. A pathologicaldiagnosis of osteoblastic osteosarcoma was suspected and was confirmed byneedle biopsy. There had been two other cases of osteosarcoma in the samefamily. The patient was treated with neoadjuvant chemotherapy followed byamputation of the arm below the elbow.